Formulation and Sensory Evaluation of Functional Cake Prepared from Sweet Potato Powder (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The present study aimed to develop and evaluate a value-added cake formulated with sweet potato powder, eggs, cocoa powder, date syrup, baking soda, baking powder, vanilla essence, and oil. Sweet potato powder was incorporated as a functional ingredient to enhance the nutritional quality of the product while maintaining acceptable sensory attributes. The prepared cake was subjected to sensory evaluation for color, texture, flavor, taste, and overall acceptability using a standard hedonic scale. The results indicated that the formulated cake possessed desirable sensory characteristics and good consumer acceptability. The inclusion of sweet potato powder contributed to improved nutritional value by increasing dietary fiber and providing natural bioactive compounds, while date syrup acted as a natural sweetener and flavor enhancer. Cocoa powder and vanilla essence helped in masking the characteristic flavor of sweet potato and improved palatability. The combined use of baking powder and baking soda ensured proper leavening and satisfactory cake volume and crumb structure. The study concludes that sweet potato powder can be successfully utilized in cake formulation to develop a nutritionally enriched bakery product with good sensory quality and potential for application in functional food development.The developed sweet potato powder cake showed good sensory quality and overall acceptability. Sweet potato powder improved the nutritional value by increasing dietary fibers, while date syrup enhanced sweetness and flavor. Cocoa powder and vanilla essence improved palatability, and proper leavening agents provided good cake texture and volume. Overall the cake proved to be a nutritious and acceptable functional bakery product.